Cultural Phenomenon And Moral Value In Short Story The Gift Of The Magi By O Henry - Heni Heni (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2022)
Literature is an imaginative works of an author. Literature is also part of culture. In a fiction or story there are some norms, values, attitude, and behavior that reflects the society in which the writer live in. There are normative function of literature in a society . So literature can also influence social change. Fiction can change economic, family, lifestyle, or attitude of a community. Society as the reader will identify themselves as the characters in the story. They will tend to feel what the characters feel and do what the characters do. One -or maybe two - values contained in the short story entitled The Gift of the Magi are social and moral values. The explanation of social and moral values itself is well known. Where social is interaction and moral is an assessment of the good and bad of a particular thing. It can be seen that moral and social values are bound to each other. It seems that reader live in the story and imagine themselves as fictional actors. Even though a fiction is an author works, it doesn’t mean that story is only an individual imaginative writer. It is the product of a society. So literature and culture of society is a unity. They influence for each other.